A light among the gentiles Jewish missionary activity in the Second Temple period - McKnight, Scot (Minneapolis, MN Fortress, 1991)
Includes bibliographical references and index.
Keywords: Judaism -- history -- postexilic period, 586 B.C.-210 A.D. -- historiography; Proselytes and proselyting, Jewish; Jews -- history -- 586 B.C.-70 A.D. -- historiography; Christianity -- origin